EFEKTIVITAS TRANSFORMASI METODE CERAMAH KE MODEL TWO STAY TWO STRAY DALAM MEMBENTUK KARAKTER RELIGIUS SISWA PADA JAM PELAJARAN KRITIS - Rahma Putri Adira Az-Zahra; Bahar Agus Setiawan; Siti Nursyamsiyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the ineffectiveness of the lecture method in Islamic Religious Education (PAI) learning at SMPN 04 Genteng, particularly during afternoon class sessions that trigger student saturation and hinder the internalization of character values. This study aims to analyze the effectiveness of transforming the learning method from the lecture pattern to the cooperative model Two Stay Two Stray (TSTS) in shaping students' religious character at SMPN 04 Genteng. The main problem raised is the low effectiveness of the lecture method during afternoon class sessions, which causes a decline in student focus and hampers the internalization of religious values. This study uses a qualitative approach with a descriptive qualitative research type focused on evaluating the learning process. Data were collected through in-depth observation, interviews with PAI teachers, and documentation of student character learning outcomes. The results show that the use of the lecture method during critical hours tends to make students passive and bored, making character values difficult to implement. Conversely, the application of the TSTS model proved effective in enlivening classroom dynamics through visiting and receiving guests activities that encourage students to actively move and communicate. This transformation significantly strengthened students' religious character dimensions, particularly in the aspects of responsibility, cooperation (ta'awun), and honesty. This study concludes that replacing the lecture method with the TSTS model is an appropriate managerial strategy to optimize the formation of students' religious character at school. Keywords: Effectiveness, Lecture Method, Two Stay Two Stray, Character, Religious